Biophysical study on the interaction of cartap hydrochloride and hemoglobin: Heme degradation and functional changes of protein. Issue 7 (20th April 2019) - Emadi, Mahdieh; Maghami, Parvaneh; Khorsandi, Khatereh; Hosseinzadeh, Reza
Abstract: Cartap hydrochloride is a mildly perilous insecticide known as "Padan" which is used largely in agricultural farms to control weevil and caterpillars. The over use of cartap causes harmful effects on human health. Since the blood may acts as a target and carrier for insecticides, the effect of these compounds on blood in mammalian toxicology is very important. Hemoglobin is a tetramer protein that play critical role in oxygen transport. The aim of this study was to analyze and compare the function and structural changes of hemoglobin in the presence of different concentrations of cartap by employing different spectroscopic techniques. The obtained results show that cartap has a high hemolytic effect which is increased with cartap concentration and reduces the thermal midpoint of hemoglobin. Fluorescence measurements reveal heme degradation at different concentrations of cartap. In consequence of theoretical and experimental results, cartap has an undesirable effect on hemoglobin structure and function.